Association between low maternal low-density lipoprotein cholesterol levels in the second trimester and delivery of small for gestational age infants at term: a case-control study of the national center for child health and development birth cohort. (18th June 2017) - Serizawa, Kana; Ogawa, Kohei; Arata, Naoko; Ogihara, Atsushi; Horikawa, Reiko; Sakamoto, Naoko
Abstract: Maternal malnutrition during pregnancy can lead to a small for gestational age (SGA) status among infants. In the present study, we compared the lipid levels during the second trimester in women who delivered SGA infants at term with those in women who delivered appropriate for gestational age infants at term, to examine whether abnormalities in maternal lipid levels could be a risk factor for the delivery of an SGA infant. We enrolled pregnant women who gave birth at the National Center for Child Health and Development (NCCHD), their infants, and who volunteered in a Birth cohort study at the NCCHD. We analyzed a total of 843 blood samples obtained from the women during the second trimester. Moreover, we used multi-regression analysis to assess the relationship between low-density lipoprotein cholesterol (LDL-C) levels during the second trimester and the risk of delivering an SGA infant. The adjusted odds ratio (OR) for LDL-C levels was 0.99 (95% CI, 0.98–0.99). These results indicate that a low LDL-C level during the second trimester was associated with an increased risk of delivering an SGA infant at term. The finding would not only help predict future SGA infant birth, but can also help prevent SGA infant birth.